'n Vergelyking tussen kinderpsigiatriese verpleging in Suid-Afrika en San Francisco - L. van Rhyn (AOSIS, 1993)
The provision of services to children with psychiatric disorders in the Republic of South Africa - especially black and underprivileged children - is limited and inadequate. The practice of the nurse in the field of child psychiatry is vague and undeveloped and there are few nurses in South Africa with the knowledge and skills to set guidelines for this area of practice. A qualitative field study was undertaken in South Africa and San Francisco to analyze, describe and compare the situation in regard to contemporary nursing practice in child psychiatry. The result showed that nurses in San Francisco were academically better qualified than their colleagues in South Africa, while many similarities regarding theraputic skills were found.